2018
DOI: 10.1371/journal.pone.0196072
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and canopy reflectance spectrometry applied to the estimation of angular leaf spot disease severity of common bean crops

Abstract: This study is aimed at (i) estimating the angular leaf spot (ALS) disease severity in common beans crops in Brazil, caused by the fungus Pseudocercospora griseola, employing leaf and canopy spectral reflectance data, (ii) evaluating the informative spectral regions in the detection, and (iii) comparing the estimation accuracy when the reflectance or the first derivative reflectance (FDR) is employed. Three data sets of useful spectral reflectance measurements in the 440 to 850 nm range were employed; measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
8
1
1
Order By: Relevance
“…However, these wavelengths were related to pigments, such as carotenoids and chlorophyll [36]. One study has shown no improvement in the models when using the blue and green spectral regions for input information [18]. In this study, we found that the leaf hyperspectral reflectance in the green region was poorly correlated with the soybean FLS classification.…”
Section: Plos Onecontrasting
confidence: 51%
See 2 more Smart Citations
“…However, these wavelengths were related to pigments, such as carotenoids and chlorophyll [36]. One study has shown no improvement in the models when using the blue and green spectral regions for input information [18]. In this study, we found that the leaf hyperspectral reflectance in the green region was poorly correlated with the soybean FLS classification.…”
Section: Plos Onecontrasting
confidence: 51%
“…Hyperspectral technique can be also used to conduct an in-depth examination of crop characters, such as crop cell structure, chlorophyll content, moisture content, trace element content, and light reflection and absorption characteristics. This may not be achieved using multispectral data, which have the relative coarse bandwidths [18]. Many studies have shown the feasibility and potential of hyperspectral reflectance data for evaluating the degree of crop diseases such as rice glume blight disease [19], black bean yellow mosaic disease [20], and citrus greening [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral reflectance measurements were taken under laboratory conditions in a dark environment admitting no light from outside. For the measurements, a spectroradiometer (ASD Inc., Boulder, CO, USA) (20)(21)(22) that can make reflectance measurements between the wavelengths of 325-1075 nm of the electromagnetic spectrum and a contact probe (plant probe) were used. Contact probe was attached to the spectroradiometer ( 23) and contain a 100 W halogen lamp as an artificial light source (24).…”
Section: Methodsmentioning
confidence: 99%
“…Crop yields predictions based on soil fertility parameters and metrological data was possible by using ANNs, thanks to its abstraction capability (Dahikar and Rode, 2014). In plant diseases, an ANN was able to estimate the severity of angular leaf spot in bean cultures, using leaf and canopy hyperspectral reflectance spectra (Martínez-Martínez et al, 2018). The use of ANNs have a widespread future in the development of new techniques, and there is more room for future research and applications of ANNs (Darji et al, 2015;Ghanbarzadeh et al, 2009;Laaboudi et al, 2012).…”
Section: Ghg Emission Reductionsmentioning
confidence: 99%